Estimating Dust Accumulation on Photovoltaic Modules in the UAE - AlArif, Amal AbdulAziz (2019)
A Master of Science thesis in Electrical Engineering by Amal AbdulAziz AlArif entitled, “Estimating Dust Accumulation on Photovoltaic Modules in the UAE”, submitted in May 2019. Thesis advisor is Dr. Mostafa Shaaban. Soft and hard copy available.